Antagonistic Action of Watermelon Juice Probioticated Using Different Strains of Lactobacilli against Salmonella typhimurium - MR Fazeli; N Amirmozafari; R Golbooi nejad; H Jamalifar (Tehran University of Medical Sciences, 2007)
Background: The aim of this study was to compare the antimicrobial activity of watermelon juice probioticated using different strains of lactobacilli against Salmonella typhimurium.Methods: Probioticated watermelon juice was produced using four strains of lactobacilli (Lactobacillus casei, L. acidophillus, L. fementum and L. plantarum). The watermelon juice was pasteurized for 30 minutes at 63º C and was inoculated with a 24 h culture of individual lactobacilli and incubated at 37º C. All of the lactobacilli were capable of growing in watermelon juice and reached a cell density of 108 CFU/ml after 48 h incubation at 37º C. Overnight culture of S. typhimurium was added to probioticated watermelon juice and reduction of the viable cells were assayed, on bismuth sulfite agar medium for 24 h. Antimicrobial activities of the lactobacilli cells against the test strain of Salmonella were also determined by measuring the diameter of growth inhibition zone in agar spot test.Rsults: All of the lactobacilli could inhibit growth of S. typhimurium with L. casei being the most potent. S. typhimurium was totally eradicated in probioticated watermelon juice after 2-6 h.Conclusion: The probioticated watermelon juices could differ in their antagonistic activities against Salmonella which could be due to the metabolite secreted by the lactic acid bacteria specially type of organic acids.